2020
DOI: 10.31299/ksi.28.2.6
|View full text |Cite
|
Sign up to set email alerts
|

Ispitivanje aktualnih trendova u korištenju društvenim mrežama kod učenika prvog i trećeg razreda srednjih škola u Hrvatskoj

Abstract: Budući da danas odrastanje gotovo neizostavno uključuje i svakodnevnu uporabu modernih tehnologija, važno je ispitati na koji način i u kojem vremenskom okviru mladi provode vrijeme na internetu i društvenim mrežama. Cilj provedenog istraživanja bio je ispitati opće navike korištenja internetom i društvenim mrežama kod adolescenata srednjoškolske dobi u Republici Hrvatskoj (N=1806). Online upitnikom, konstruiranim za potrebe ovog istraživanja putem Google Forms platforme, ispitana je nekolicina čimbenika provo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
4

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 7 publications
(7 reference statements)
0
7
0
4
Order By: Relevance
“…5-8 h per day; and 4. more than 8 h per day). Although YouTube had been classified as a social network, it was excluded from this study because it is primarily used for watching videos, i.e., for consuming content [78], and, to a lesser extent, for direct sharing and everyday communication. To answer specific research hypotheses, a new variable was created related to the frequency of use of at least one social network and was recoded into a total of five categories [(1) less than every day; (2) 1-3 h per day; (3) 3-5 h per day; (4) 5-8 h per day; and (5) more than 8 h per day].…”
Section: Methodsmentioning
confidence: 99%
“…5-8 h per day; and 4. more than 8 h per day). Although YouTube had been classified as a social network, it was excluded from this study because it is primarily used for watching videos, i.e., for consuming content [78], and, to a lesser extent, for direct sharing and everyday communication. To answer specific research hypotheses, a new variable was created related to the frequency of use of at least one social network and was recoded into a total of five categories [(1) less than every day; (2) 1-3 h per day; (3) 3-5 h per day; (4) 5-8 h per day; and (5) more than 8 h per day].…”
Section: Methodsmentioning
confidence: 99%
“…In a survey conducted on high school students in Rijeka, Malkoč (2019) found that 98.6% of adolescents use social media, usually 3 to 4 hours daily. Buljan Flander et al (2020) observed that adolescents in Croatia use YouTube, Instagram, WhatsApp, and Snapchat most often, with more than 70% of participants spending between 1 and 5 hours daily. Also, 50% of participants check their notifications as soon as they receive them.…”
Section: Adolescents On Social Mediamentioning
confidence: 99%
“…Other users can react to the posts by liking them. As previously mentioned, Instagram is among most popular social media in general population (Statista, 2022), as well as adolescents (Anderson & Jiang, 2018;Buljan Flander et al, 2020).…”
Section: Types Of Social Media Usementioning
confidence: 99%
“…Na temelju opsežnog pregleda literature i statističkih pokazatelja uočava se kako su adolescenti sve češći korisnici različitih društvenih mreža (1)(2)(3)(4). Cheung i sur.…”
Section: Uvodunclassified
“…U začetcima istraživanja online navika adolescenata interes je bio najviše usmjeren na Facebook, tada najpopularniju društvenu mrežu, no istraživanje na reprezentativnom uzorku europskih adolescenata pokazalo je kako adeloscenti danas češće koriste Instagram i Snapchat koji im nude izražavanje prevladavajuće u obliku fotografija i videa (4). Kao najpopularnije društvene mreže među adolescentima u Hrvatskoj trenutno se ističu Instagram, YouTube, Snapchat i TikTok (1,3).…”
Section: Uvodunclassified